La reconstruction du Mexique au xxie siècle et les voies du changement en Amérique latine - Sergio Zermeño (Cahiers des Amériques Latines)
Mexican reconstruction in the 21th century and the Ways of change in Latin America. From a comparative perspective (with special reference to Brazil), this article analyzes the reasons that explain the lack of continuity and the rapid emergence and sudden disappearance that have characterized social struggles and their organizational apparatuses in Mexico. It also analyzes whether it will be possible to construct a new culture of harmony and balance in consumption and the relationship with nature on the basis of local and regional arrangements, within the framework of globalized capitalism, or whether this culture should be framed as an anti-capitalist struggle, yet without violence and precipitation.